UM ENSAIO SOBRE AS POTENCIALIDADES DO USO DO CONCEITO DE GÊNERO NA ANÁLISE GEOGRÁFICA (Revista de História Regional, 2007)
This work explores the potentialities of the concept of genre for the geographical analysis, emphasizing the difficulties inherent to the power relations that sustain the process of geographical knowledge production and the invisibility of women as an urban space producer agent. Besides that, it presents a series of works by American andEnglish women authors and proposes research to be developedwithin the Brazilian geography field.